Persepsi Mahasiswa Non Muslim Terhadap Bank Syariah Indonesia: Studi Pada Mahasiswa UNJA - Nurhaya Nurhaya; Addiarrahman; Erwin Saputra Siregar (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
The aim of this research is to determine the perceptions of non-Muslim students towards Indonesian Sharia Banks. To answer this problem, this research was conducted using descriptive qualitative research with data sources from UNJA students. The data collection techniques used were interviews, observation and documentation. The results of this research show that students' perceptions of sharia banks are still lacking because they do not understand sharia banking, they are not sure what sharia banks are, but they have heard about sharia banks from their neighbors. They stated that Islamic banks are the same as regular banks, only that they are designed specifically for Muslims and their operational procedures are the same. Therefore, Islamic banks cannot be accessed by non-Muslim students. From the results of the research conducted, it can be concluded that in UNJA non-Muslim students' perception of sharia banking is a process of integrating, regarding and interpreting information received by the sensory system. Non-Muslim students at UNJA only know about sharia banks, some also know about them from social media, and their response to sharia banks is only ordinary banks and there are also those who say sharia banks are good banks